Student-Guided Math Practice in Elementary School: Relation among Math Anxiety, Emotional Self-Efficacy, and Children's Choices When Practicing Math - Aditi Tarkar; Brandie Matalka; Macey Cartwright; Heidi Kloos (MDPI AG, 2022)
In the current study, we explored math anxiety in the context of a special kind of math practice, one that allowed for some flexibility on the part of the students. Such student-guided math practice is conducive to exploring how math anxiety relates to children's day-to-day experiences with math, potentially yielding insights into math anxiety that would not be available otherwise. Students in Grades 3 and 4 (N = 26) could choose math problems that were below, at, or above their proficiency level. They also completed a math-anxiety survey and an emotional self-efficacy survey. Descriptive results revealed that math anxiety was implicated in two negative outcomes of math practice: children's tendency to avoid challenging math problems and children's relatively low success rate when working on class-level math. Finding that math anxiety relates to several negative experiences could explain why math anxiety can persist. Importantly, results show that emotional self-efficacy plays a role in both children's willingness to challenge themselves and their success rate. This adds to the ongoing discussion on whether emotional self-efficacy can compensate for the negative effects of math anxiety.